Hydrotreatment of lignin dimers over NiMoS-USY: effect of silica/alumina ratio. Issue 13 (14th June 2021) - Salam, Muhammad Abdus; Cheah, You Wayne; Ho, Phuoc Hoang; Olsson, Louise; Creaser, Derek
Abstract : Catalyst with a suitable balance between acidity and pore accessibility needed for lignin hydrotreatment. Abstract : Sulfides of NiMo over a series of commercial ultra-stable Y zeolites were studied in an autoclave reactor to elucidate the effect of silica/alumina ratio (SAR = 12, 30, and 80) on the cleavage of etheric C–O (β-O-4) and C–C (both sp 3 –sp 2 and sp 2 –sp 2 ) linkages present in native/technical lignin and lignin derived bio-oils. 2-Phenethyl phenyl ether (PPE), 4, 4-dihydroxydiphenylmethane (DHDPM), and 2-phenylphenol, (2PP) were examined as model dimers at 345 °C and 50 bar of total pressure using dodecane as the solvent. The etheric C–O hydrogenolysis activity was found to be in the order NiMoY30 > NiMoY12 > NiMoY80, despite a high initial rate of C–O cleavage over NiMoY12 owing to its high acid density. A high degree of hydrodeoxygenation (HDO) and hydrocracking reactions were observed with NiMoY30 yielding >80% of deoxygenated products of which ∼58% are benzene, toluene, and ethylbenzenes. A similar experiment with DHDPM showed the rapid cleavage of the methylene-linked C–C dimer (sp 3 –sp 2 ) to phenols and cresols even with the low acid density (high SAR) catalyst, NiMoY80. Direct hydrocracking of the recalcitrant 5-5′ linkage in 2PP is very slow, however, it cleaved via a cascade of HDO, ring-hydrogenation, and hydrocracking reactions. A high degree of hydrogenolysis and hydrocracking occurs over NiMoY30 due to suitable balance between acidity and pore accessibility, enhanced proximity between acidic and deoxygenation sites leading to a slightly higher dispersion of Ni promoted MoS2 crystallites. Overall, the product spectrum consisted of a high yield of deoxygenated products. The carbon content on the recovered catalyst was in the range of 3–7 wt%. These results pave the way for effective catalysts to break recalcitrant linkages present in lignin to obtain a hydrocarbon-rich liquid transportation fuel. An experiment with Kraft lignin over NiMoY30 shows good selectivity for deoxygenated aromatics and cycloalkanes in the liquid phase.